Analysis of the Budget and Realization of Regional Expenditure of the Health Department of the Province of North Sumatra During the Covid-19 Pandemic - M. Farhan Lubis; Oktarini Khamilah Siregar (International Forum of Researchers and Lecturers, 2022)
This research is entitled